Enhancing Religious Education at Al-Qur'an Education Park: A Holistic Approach - Anis Farihah; Khoiri Khoiri (Universitas Muhammadiyah Sidoarjo, 2023)
This scholarly article advocates for a holistic approach to religious education within non-formal institutions like Al-Qur'an Education Park (TPQ). While acknowledging the significance of al-Qur'an reading proficiency, the study underscores the need to broaden the curriculum to encompass diverse subjects, including contextual comprehension, ethical teachings, and Islamic history. Emphasizing teacher training diversity, the research suggests expanding pedagogical methodologies and classroom management techniques tailored to different age groups and learning styles. Moreover, resource diversification is proposed through the integration of multimedia materials, interactive activities, and contemporary discussions related to Islam, fostering student engagement and relevance. By procuring prayer guidebooks and daily prayers and considering a wider range of resources, the implications of this study point toward a dynamic and enriched learning environment that goes beyond rote learning, with potential implications for religious education strategies on a global scale. Highlight: Comprehensive Curriculum: This article underscores the importance of expanding the curriculum in non-formal religious education settings, emphasizing contextual comprehension, ethical teachings, and Islamic history alongside al-Qur'an reading. Diverse Teacher Training: The study suggests enhancing teacher training with diverse pedagogical methodologies and classroom management techniques suited to varying age groups and learning styles, thus improving educators' effectiveness. Engagement Through Resources: Resource diversification, including multimedia integration, interactive activities, and contemporary discussions, is advocated to foster student engagement and relevance, offering a dynamic and enriched learning environment beyond traditional rote learning approaches. Keyword: Religious Education, Holistic Approach, Curriculum Enrichment, Teacher Training, Resource Diversification